Eosin y triplet state as a probe of spatial heterogeneity in microcrystalline cellulose - Rodriguez, Hernan Bernardo (2012)
The photophysical behavior of eosin Y adsorbed onto microcrystalline cellulose was evaluated by reflectance spectroscopy, steady-state fluorescence spectroscopy and laser induced time-resolved luminescence. On increasing the concentration of the dye, small changes in absorption spectra, fluorescence redshifts and fluorescence quenching are observed. Changes in absorption spectra point to the occurrence of weak exciton interactions among close-lying dye molecules, whereas fluorescence is affected by reabsorption and excitation energy trapping. Phosphorescence decays are concentration independent as a result of the negligible exciton interaction of dye pairs in the triplet state. Lifetime distribution and bilinear regression analyses of time-resolved phosphorescence and delayed fluorescence spectra reveal the existence of two different environments: long-lived, more energetic triplet states arise from dyes tightly entrapped within the cellulose chains, while short-lived, less-energetic states result from dyes in more flexible environments. Stronger hydrogen bond interactions between the dye and cellulose hydroxyl groups lead in the latter case to a lower triplet energy and faster radiationless decay. These effects, observed also at low temperatures, are similar to those encountered in several amorphous systems, but rather than being originated in changes in the environment during the triplet lifetime, they are ascribed in this case to spatial heterogeneity. © 2012 Wiley Periodicals, Inc.